Update, Clinical Approach, and Clinicoradiological Correlation of Pleural Effusion: A Narrative Review - Michel Hernandez; William Prada; Andrea Alba; Nicolás Bastidas; Juan Bolivar (Sonography, 2026)
ABSTRACT Pleural effusion is a common condition worldwide. Its causes are diverse and include both local and systemic diseases, as well as benign and malignant disorders. An appropriate diagnostic approach is essential not only to identify the underlying etiology but also to guide the most suitable treatment. Pleural effusion is frequently detected as an incidental finding on thoracic imaging; however, imaging studies are only one component of the diagnostic workup, and a complete clinical history, laboratory evaluation, and, in many cases, invasive procedures are required to establish its origin. This review summarizes key aspects of pleural effusion, including its pathophysiology, clinical diagnostic approach, radiologic findings, and invasive procedures useful for both diagnosis and treatment, as well as their potential complications. Its purpose is to provide healthcare professionals with a practical reference document containing the most relevant information on this condition.